O10.2. DEFICIENT VISUAL ODDBALL STIMULUS PROCESSING PREDICTS PSYCHOSIS ONSET: RESULTS FROM THE NORTH AMERICAN PRODROME LONGITUDINAL STUDY. (18th May 2020) - Hamilton, Holly; Roach, Brian; Bachman, Peter; Belger, Aysenil; Carrion, Ricardo; Johannesen, Jason; Light, Gregory; Niznikiewicz, Margaret; Addington, Jean; Bearden, Carrie; Cadenhead, Kristin; Cornblatt, Barbara; et al.
Abstract: Background: Clinical outcomes vary among young people with the psychosis risk syndrome (PRS), with approximately 20% of individuals progressing to a psychotic disorder over 2–3 years and 30% achieving clinical remission. The identification of neurophysiological abnormalities associated with schizophrenia that predate and predict psychosis onset may enhance the accuracy of clinical outcome prediction in the PRS and help elucidate the pathogenic mechanisms of psychosis onset. Auditory P300 event-related potential (ERP) component amplitude reductions are well established in schizophrenia and reflect early attention-mediated information processing deficits. Recent studies employing auditory oddball tasks have shown that P300 amplitude deficits in PRS individuals are associated with later clinical outcomes, including both conversion to full-blown psychosis and remission from the at-risk state. The present study examined whether these effects extend to P300 in the visual modality using visual oddball task data collected as part of the North American Prodrome Longitudinal Study. Specifically, we evaluated whether visual P300 amplitudes are reduced in the PRS and predict future clinical outcomes. Methods: 540 individuals meeting PRS criteria and 229 healthy individuals completed baseline EEG recording during a visual oddball task. Visual P300 subcomponents were measured in response to two stimulus types: (1) infrequent target stimuli, reflecting top-down allocation of attention (target P3b), and (2) infrequent non-target novel distractor stimuli, reflecting bottom-up orienting of attention (novelty P3a). P300 amplitudes of PRS participants who converted to psychosis (n=70) were compared with those of PRS non-converters who were followed clinically for 24 months and continued to be symptomatic (n=131) or fully remitted from the PRS (n=87). Results: Group comparison effects did not differ by stimulus type. Visual P300 amplitudes were not significantly reduced in the PRS group relative to healthy individuals (p=.25). However, baseline target P3b and novelty P3a amplitudes were reduced in PRS individuals who later converted to psychosis relative to all PRS non-converters, including those who remitted (p=.006, d=.44) and those who remained symptomatic (p=.015, d=.37), as well as healthy individuals (p=.001, d=.44). Baseline P300 amplitudes were similar among healthy controls, PRS remitters, and PRS individuals who remained symptomatic (ps>.45). Moreover, visual P300 amplitudes differentiated future psychosis converters after accounting for PRS symptom severity. Finally, both target P3b and novelty P3a amplitudes predicted the time to psychosis onset in PRS participants (p=.03 and p=.02, respectively), such that more deficient P300 amplitudes were associated with shorter time to conversion. Discussion: Baseline visual P300 amplitudes were reduced in future PRS converters relative to non-converters, with effect sizes comparable to those reported in previous auditory P300 studies of the PRS. Results implicate visual P300 as a neurophysiological vulnerability marker that predicts clinical outcomes among PRS individuals, including future transition to psychosis. Accordingly, together with prior auditory P300 studies, results suggest that P300 may have the potential to contribute to personalized early intervention in the PRS by distinguishing individuals with the greatest risk for psychotic illness, who require the most aggressive treatment, from those who may need minimal intervention.